Integrated Marketing Communication Kedai Pantry Magetan Pada Era Digitalisasi 4.0 - Hilda Yunita Wono; Nafiah Ariani; Azalea Abril Hermanto; Bunga Feby Nabilla (Jurnal Spektrum Komunikasi, 2022)
Integrated marketing communications or IMC that is implemented in a business well can make a significant increase to a company's revenue. This is what makes Kedai Pantry Magetan to carry out IMC activities. The Pantry Shop, which started a business during the Covid-19 pandemic, used IMC as a way of promotion so that the shop could still operate even during the pandemic. This research was conducted using a qualitative descriptive method to dissect the IMC Kedai Pantry strategy. This study shows what activities are carried out as well as interviews with shop owners in order to find out the reasons for using this strategy. Of the seven IMC activities used by the pantry shop, online marketing, direct marketing, sales promotion, public relations and advertising. From the IMC activities carried out to help the shops that were established during this pandemic to survive until now.